2017
DOI: 10.1111/cdev.12764
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Household Food Insecurity in Early Childhood and Children's Kindergarten Skills

Abstract: Using nationally representative data on a recent birth cohort of U.S.-born children in low-income households (n = 2,800-3,700), this study investigates associations between the timing and intensity of early childhood food insecurity and children's kindergarten reading, math, and social-emotional outcomes. Descriptive patterns reveal that approximately 20% of low-income 0- to 5-year-old children reside in food-insecure households. Food insecurity experienced during early childhood is unfavorably associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 77 publications
(86 reference statements)
3
93
0
1
Order By: Relevance
“…47,53 In addition, three longitudinal studies showed a detrimental effect of FI on mental health markers, such as social skills, internalising and externalising behaviours and hyperactivity. 39,89,96 By contrast, another longitudinal study did not find an association between FI and the developmental change in children's behavioural problems. 93 The authors suggested that the impact of FI on children's behaviour could be episodic or could interact with developmental phases over time.…”
Section: Mental Health Outcomesmentioning
confidence: 93%
See 3 more Smart Citations
“…47,53 In addition, three longitudinal studies showed a detrimental effect of FI on mental health markers, such as social skills, internalising and externalising behaviours and hyperactivity. 39,89,96 By contrast, another longitudinal study did not find an association between FI and the developmental change in children's behavioural problems. 93 The authors suggested that the impact of FI on children's behaviour could be episodic or could interact with developmental phases over time.…”
Section: Mental Health Outcomesmentioning
confidence: 93%
“…In total, 17 studies 19,26,39,41,47,53,54,69,73,76,89,92,93,96,99,106,108 investigated the association between FI and children's mental health outcomes. Fourteen studies adjusted their analyses for explanatory or confounding variables ( In summary, 7 out of the 14 studies that adjusted their analyses for explanatory or confounding variables found an association between FI and children's emotional or behavioural problems, 19,26,54,69,76,92,108 one found an association between FI and children's mental health symptoms, 106 and two reported an association between FI and children's mental health disorders.…”
Section: Mental Health Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Food insecurity increases a child’s risk for asthma, with increased odds in Hispanic children compared to non-Hispanic Whites and Blacks, (Mangini, Hayward, Dong, & Forman, 2015); iron deficiency anemias (Eicher-Miller, Mason, Weaver, Mccabe, & Boushey, 2009); developmental issues in infants and toddlers, (Rose-Jacobs et al, 2008); growth stunting, (Bernal, Frongillo, Herrera, & Rivera, 2014); poor social, emotional, and cognitive skills needed for the Kindergarten year (Johnson & Markowitz, 2017); and absenteeism from school (Bernal et al, 2014). …”
Section: Three Exemplars Of Child Povertymentioning
confidence: 99%